Generator Dynamic Response Analysis and Improvement Following Distribution Network Disturbance - Mirza Saric (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Use of renewable energy sources for the purposes of electricity generation is increasing throughout the world. Connection of new generators, however, introduces significant challenges to power network operators and managers. The power system transient stability is affected by the grid connection of new generation units. The objective of this paper is to investigate asynchronous generator dynamic response issues and capabilities under three phase symmetrical fault conditions and to propose a methodological approach to designing a generator transient stability solutions. Analysis and methodology are introduced through a realistic generator connection example. Simulations show that power system stability can be significantly affected by the connection of new generators and that this phenomena needs to be carefully considered during the connection planning process. This paper is a part of an ongoing research on the distributed generation impact on power network and its aim is to provide two main contributions to the existing body of knowledge. Firstly, it is expected that this paper will contribute toward a better understanding of the influence that generators have on the power system transient stability. Secondly, this paper is expected to contribute towards the practical understanding of fundamental power system transient stability improvement solutions.